Pemberdayaan Kader Kesehatan dalam Deteksi dan Pemantauan Ekspresi Emosi Keluarga dari Orang dengan Skizofrenia di Muara Kumpeh - Daryanto Daryanto; Mohd. Syukri (Jurnal Abdimas Kesehatan (JAK), 2026)
Background: High emotional expression is a phenomenon often experienced by families of patients with mental disorders such as schizophrenia. Families need support from health workers, including health cadres in dealing with the problems of caring for their families. Empowerment of health cadres in detecting and monitoring the emotional expressions has never been done. The activity goals is to empower health cadres in detecting and monitoring the emotional expressions of families of patients with mental disorders in the Muara Kumpeh  Community Health Center area. Method: The community service activity is carried from April to October 2025. These involved 30 people from a total of 130 health cadres from working area. Participants were given education and a guidebook, followed by training on how to detect and monitor the emotional expressions of patients' families using the handbook, as well as how to make reports and case referrals.Result : The empowering activities could increased the average knowledge score for detecting and monitoring emotional expressions of families of patients with mental disorders from 5,73 to 8.87. Almost all cadres have utilized the handbook to detect and monitor emotional expressions and included it in monthly activities and are able to refer families who are detected with heightened emotional expressions. Conclusion: These empowerment have increased the knowledge and skill in detection and monitoring the family of patient emotion. Those responsible for mental health programs were expected to monitor the performance of cadres in detecting and monitoring family emotions and request reports regularly every month.